Parametric investigation of synthetic jet and its boundary layer control - Kim, Y-H. (Cranfield University, 2005)
The potential for active control of low Reynolds number boundary layers using synthetic jet generators (SJG) has been established. The results from a four stage experimental study are presented in which the operational and geometric parameters of a rectangular slot choice SJG are optimised. A time-dependent, analysis of the SJG velocity profile is carried out in quiescent conditions prior to application of the SJG in (i) a nominally zero pressure gradient at plate boundary layer (l.54><l05<ReX<2.86><l05), and (ii) a simulated longitudinal pressure gradient, in order to asses the impact of the device on boundary layer development downstream A piezoelectric driven synthetic jet is used in this study in which the resonance characteristics of an intimal cavity are used to establish a fluid jet. Two characteristic resonance frequencies are identified; the mechanical resonance frequency of the diaphragm (FD), and the acoustic resonance frequency of the cavity (FC). The latter is shown to be the most energy efficient excitation frequency in terms of creating the highest synthetic jet velocity. Since the optimum operational and geometrical parameters are difficult to predict theoretically, a parametric study is presented in which, for a constant slot width (H=0.28mm) and resonance cavity geometry, an optimum slot length (L/H=l7.86~2l.43), which creates the highest synthetic jet velocity, can be established. Similarly, for a constant resonance cavity diameter, a narrower resonance cavity results in a higher synthetic jet velocity. Although not a experimental parameter, diaphragm clamping force is also seem to be significant in terms of synthetic jet velocity. When studied in conjunction with a zero-pressure gradient boundary layer - such that the jet exits normal to the surface -the orientation of the rectangular slot relative to the freestream (ß) is seen to result in a flow downstream of the slot which changes from a counter rotating vortex pair (when ß=0°) to a single streamwise vortex (when ß=20°). Increasing the slot angle beyond 20° diminishes the induced vortex structure such that, at ß=90°, the effect is similar to a surface obstruction. A time dependent analysis of the synthetic jet velocity profile shows that the jet has a structured fluctuation which, in the longitudinal sense, is strongest in the middle of slot (X/H=O, Y/I-I=0) and in a plane close to the slot (Z/H=3). The suction stroke of the synthetic jet is seen to induce a flow in the surrounding air which is identified by measurements at various lateral locations with a single component HWA probe. When a dual diaphragm is used for a SJG, synchronisation of the diaphragm displacement is seen to be important. If the velocity peaks corresponding to each diaphragm occur at a different phase in the excitation cycle, the performance increase attributed to the dual diaphragm operation is reduced. Studies of SJG effectiveness within a 2D boundary layer subjected to a controlled longitudinal pressure gradient show that activation of the SJG can both trigger laminar-turbulent transition and eliminate a laminar separation bubble. The potential for low Reynolds number flow control by virtual aeroshaping is therefore demonstrated.